Ambient Temperature–Corrected Mechanical Stress Mapping of Gallium Nitride and Aluminum Indium Gallium Phosphide Films by Raman Scattering Spectroscopy for Characterization of Light‐Emitting Diodes. Issue 7 (6th February 2020) - Guo, Xiaoru; Mughal, Asad; Dunphy, Darren; Stone, Gregory; Miller, David; Huh, Sungwook
Abstract : Raman spectroscopy can provide a detailed analysis of mechanical stress in crystalline materials through the measurement of shifts in vibrational frequency. However, the ambient temperature drift during measurements can lead to inaccurate mechanical stress values. Herein, the 2D Raman mapping analysis of gallium nitride (GaN) and aluminum indium gallium phosphide (AlInGaP) epitaxial films within packaged light‐emitting diode (LED) devices reveals micrometer‐scale localized stress distributions. A temperature‐corrected measurement method is developed to evaluate the mechanical stress of InGaN LED dies at various LED operating conditions. The impact of die design on mechanical stress is studied for both GaN on Al2 O3 (chip scale package, CSP) and GaN thin‐film flip chip (TFFC) designs. Raman mapping of AlInGaP LEDs is also demonstrated and shows comparable resolution with the GaN LED results. Abstract : Herein, a method to correct the Raman system drift induced by ambient temperature variations for epitaxial film mechanical stress evaluations is demonstrated. The developed mechanical stress mapping method can reveal microlevel mechanical stress within an epitaxial crystal film and is used to compare commercially available light‐emitting diodes (LEDs). The design and package effects of LEDs are analyzed.